Readings : The Poetics of Blanchot, Joyce, Kakfa, Kleist, Lispector, and Tsvetayeva - Cixous, Helene, 1937- (Book collections on Project MUSE., 1991)
A leader in the feminist intellectual movement, Cixous presents this highly informative meditation on ethics and poetics which draws on philosophy and psychoanalysis.